Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Manajemen Pengelolaan Keuangan pada Sales Elektronik di Palembang - Mentari Khikhim; Isni Andriana; Kemas Muhammad Husni Thamrin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of financial literacy and financial behavior on financial management in electronic sales in Palembang. This study uses a quantitative approach with data collection techniques through questionnaires. The sample in this study is 100 electronic sales in Palembang using random sampling techniques. The data analysis technique in this study uses multiple linear regression analysis. The research data was processed using the Statisfical Product and Service Solutions (SPSS) program. The results of the study show that financial literacy and financial behavior have a positive and significant effect on financial management on electronic sales in Palembang.